A 3D printed TCP/HA structure as a new osteoconductive scaffold for vertical bone augmentation. Issue 1 (28th October 2014) - Carrel, Jean‐Pierre; Wiskott, Anselm; Moussa, Mira; Rieder, Philippe; Scherrer, Susanne; Durual, Stéphane
Abstract: Introduction: OsteoFlux ® (OF) is a 3D printed porous block of layered strands of tricalcium phosphate (TCP) and hydroxyapatite. Its porosity and interconnectivity are defined, and it can be readily shaped to conform the bone bed's morphology. We investigated the performance of OF as a scaffold to promote the vertical growth of cortical bone in a sheep calvarial model. Materials and methods: Six titanium hemispheres were filled with OF, Bio‐Oss (particulate bovine bone, BO), or Ceros (particulate TCP, CO) and placed onto the calvaria of 12 adult sheep (6 hemispheres/sheep). Histomorphometric analyses were performed after 8 and 16 weeks. Results: OF led to substantial vertical bone growth by 8 weeks and outperformed BO and CO by a factor 2 yielding OF 22% ± 2.1; BO 11.5% ± 1.9; and CO 12.9% ± 2.1 total new bone. 3 mm away from the bony bed, OF led to a fourfold increase in new bone relative to BO and CO ( n = 8, P < 0.002). At 16 weeks, OF, BO, and CO behaved similarly and showed marked new bone synthesis. A moderate degradation was observed at 16 weeks for all bone substitutes. Conclusion: When compared to existing bone substitutes, OF enhances vertical bone growth during the first 2 months after implantation in a sheep calvarial model. The controlled porous structure translated in a high osteoconductivity and resulted in a bone mass 3 mm above the bony bed that was four times greater than that obtained with standard substitutes. These results are promising but must be confirmed in clinical tests.